Evaluate the Efficacy of Coronary by Computed Tomography vs Coronary Angiography in the Patients Undergoing Valve Surgery - Sajid Ali, Ahmad Tariq, Shoeb Abid (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: The study was conducted to assess the efficacy of coronary computed tomography for coronary evaluation in patients undergoing valvular surgery, keeping coronary angiography as gold standard. Methodology: This prospective study was conducted in the Department of Cardiology of Punjab Institute of Cardiology, Lahore from January 2023 to June 2023. A total of 100 patients with valvular heart disease undergoing preoperative coronary evaluation were included in the study. All patients underwent computed tomography angiography and coronary angiography within 7 days of admission. Angiography was performed by cardiologists with at least 10 years or more experience of catheterization with common femoral artery or radial artery as a puncture site. Dual source 64 CT system with non-ionic, low-osmolar contrast was used to perform CCTA. Each 18 segment of coronary artery was evaluated separately, main coronary artery was assessed as a whole and significant stenosis in each patient evaluated. Results: The results showed that in total, 1800 segments were evaluated, among which 270 were excluded due to being absent, hence, 1530 segments were used for final comparison. 1056 (68.3%) were normal, 459 (30%) had insignificant stenosis, 77 (5%) had significant stenosis and 10 (0.6%) were completely occluded on CCTA. CCTA had a sensitivity of 88.3%, sensitivity of 98.5%, positive predictive value of 86.6%, negative predictive value of 98.5% and overall accuracy of 98.9% for identification of significant stenosis in segments. An overall sensitivity for all vessels was 85%, specificity & positive predictive value was 100% and negative predictive value was 98% indicating excellent accuracy of 98%. Conclusion: In conclusion, coronary computed tomography angiography has a high diagnostic accuracy for detecting coronary artery disease and stenosis in patients before valvular surgery. Keywords: Angiography, Computed tomography, Stenosis, Valvular disease